A Seamless Connection: Evaluating the Integration and Linkage Between Medical Clinics and Pharmacy Departments for Improved Patient Outcomes - Yuossef Ali Hamad Alyami; Zayed Mohammad Almushref; Salem Mana Rashed Al Khuraym; Muteb Ali Mohammed Alyami; Mohammed Ali Mohammed Al Mahari (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2022)
This article examines the critical integration of medical clinics and pharmacy departments, focusing on how such linkage can enhance patient outcomes. Historically, medical clinics and pharmacy departments have operated in silos, leading to challenges in healthcare delivery, including inefficiencies and increased healthcare costs. This piece explores the theoretical and practical benefits of a more integrated approach, drawing upon real-world case studies where such strategies have been successfully implemented. It delves into the logistical, cultural, and technological barriers that impede this integration and offers strategic solutions to overcome these obstacles. The article provides a comprehensive analysis of the impact of this integration on patient outcomes, highlighting improvements in patient care, reduction in medication errors, and enhancements in overall health system efficiency. Additionally, it speculates on the future directions of integrated healthcare systems, considering potential innovations and research areas. This comprehensive review underscores the necessity of a seamless connection between medical clinics and pharmacy departments, advocating for a patient-centered approach in healthcare systems.